The Federal Democratic Republic of Ethiopia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This IMF Staff Report for 2017 Article IV Consultation highlights that Ethiopia has recorded annual average GDP growth of about ten percent in the last decade, driven by public investments in agriculture and infrastructure. The poverty rate has fallen from 44 percent in 2000 to 23.5 percent in 2015/16. In 2016/17 GDP growth is estimated at 9 percent, as agriculture rebounded from severe drought conditions in 2015/16. Industrial activity expanded, with continued investments in infrastructure and manufacturing. The current account deficit declined in 2016/17 to 8.2 percent of GDP. Over the medium term, growth is expected to remain about 8 percent, supported by sustained expansion in exports and investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet